Catalytic performance of a hydrogen fuel cell with platinum nanomaterials-coated gas diffusion layer - Monserrat, Richard Centilles (Animo Repository, 2012)
The synthesis of platinum nanomaterials was done using Horizontal Vapor Phase Crystal (HVPC) growth technique for hydrogen fuel cell application. Thirty five milligrams of platinum powder with 99.99% purity was used in the synthesis. Growth temperature was set to 8000C, 10000C and 12000C, growth times were 10 hours and 12 hours with ramp time was set to 60 minutes. Characterization of platinum nanomaterials was done using Scanning electron Microscope (SEM) and Energy Dispersive X-ray (EDX). SEM was used to investigate the surface morphology and EDX was used to determine the elemental composition of platinum nanomaterials deposited in the substrate. Results show that platinum nanomaterials with diameter less than 100 nm are dispersed into substrate. The optimum result can be done at growth temperatures of 10000C and 12000C and growth times of 10 hrs and 12 hrs. Synthesized platinum nanomaterials are used for hydrogen fuel cell application. This study found out that 0.93 V off-voltage can be produced by hydrogen fuel cell with platinum nanomaterials. When it is connected to a propeller (2.3 ohms), hydrogen fuel cell can produced 0.76 V. This study varied the oxygen supplied to hydrogen fuel cell with platinum nanomaterials. It was found out that the hydrogen fuel cell with platinum nanomaterials only produced 0.47 V when supplied by ambient air. The voltage time graph for hydrogen fuel vi De La Salle University cell with platinum nanomaterials was utilized to determine the Faraday efficiency. Result shows that hydrogen fuel cell with platinum nanomaterials has Faraday Efficiency of 48.61%. This study further proves that HPVC growth technique is capable of producing platinum nanomaterials. This study is also in line with others in concluding that platinum nanowires used as catalyst in hydrogen fuel cell give significant effect to the production of voltage.